2023
DOI: 10.1002/mdc3.13737
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Movement Disorders Commonly Seen in Asians

Abstract: The increasing availability of molecular genetic testing has changed the landscape of both genetic research and clinical practice. Not only is the pace of discovery of novel disease-causing genes accelerating but also the phenotypic spectra associated with previously known genes are expanding. These advancements lead to the awareness that some genetic movement disorders may cluster in certain ethnic populations and genetic pleiotropy may result in unique clinical presentations in specific ethnic groups. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 196 publications
(422 reference statements)
0
3
0
Order By: Relevance
“…PRRT2 mutations can be associated with a spectrum of disorders from benign familial infantile epilepsy and infantile convulsion to PKD. This and the prevalence of PKD, suggesting that it is more common in Asians, have been reviewed elsewhere by the TF [ 167 ].…”
Section: Resultsmentioning
confidence: 99%
“…PRRT2 mutations can be associated with a spectrum of disorders from benign familial infantile epilepsy and infantile convulsion to PKD. This and the prevalence of PKD, suggesting that it is more common in Asians, have been reviewed elsewhere by the TF [ 167 ].…”
Section: Resultsmentioning
confidence: 99%
“…ET is commonly diagnosed, but it seems that this is rarely sufficiently severe in Malaysian patients to be considered for neurosurgical treatment, again suggesting potential ethno-geographic differences in the expression of movement disorders. 29,46 In a survey of experts from Asia, it was reported that only a "very low" number of essential tremor patients undergo functional neurosurgery in India, although in Japan 210 cases were treated with focused ultrasound lesioning over a three-year period (2016-2019). 11 Our study has several strengths and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Results of testing for monogenic and GBA1-related PD (which prioritized familial and/or EOPD cases) were available for 61 patients: next generation sequencing-based PD gene panel (n=21), 15 multiplex ligation-dependent probe amplification (n=13), 28 and/or whole genome sequencing (n=44, under the Global Parkinson's Genetics Project [GP2]). 17 Twelve (19.7%) were found to have variants in the risk factor GBA1 gene (n=10), 15,29 and in the monogenic LRRK2 (n=1) 30 or PRKN genes (n=1) 28 (Supplementary Table 3). Among the patients with GBA1 variants, only two were able to have their LEDD substantially reduced (by 30% or 50%) post-operatively.…”
Section: Pd Patientsmentioning
confidence: 99%
“…Notably, a significant number of genetic movement disorders (eg, Wilson's disease, several spinocerebellar ataxias, PLA2G6-related parkinsonism, and neuronal intranuclear inclusion disease), or specific genetic variants (eg, p.L347P mutations in PINK1 causing early-onset PD), are more commonly encountered in LMICs. 38,39,[41][42][43] Funding bodies, industry, and research institutes should actively encourage the participation of patients and researchers from such populations in clinical trials. (8) Promoting advocacy for patients with genetic disorders to positively impact healthcare and social policies, including efforts to reduce stigma.…”
Section: Acceptability-are Our Patients and Societies Ready?mentioning
confidence: 99%